The exposed N-terminal tail of the D1 subunit is required for rapid D1 degradation during photosystem II repair in Synechocystis sp PCC 6803 - Komenda, Josef; Tichý, Martin; Prášil, Ondřej; Knoppová, Jana; Martínková, Stanislava; Vries, de Remco; Nixon, Peter J (The Plant cell, 2007)
The selective replacement of photodamaged D1 protein within the multisubunit photosystem II (PSII) complex is an important photoprotective mechanism in chloroplasts and cyanobacteria. FtsH proteases are involved at an early stage of D1 degradation, but it remains unclear how the damaged D1 subunit is recognized, degraded, and replaced. To test the role of the N-terminal region of D1 in PSII biogenesis and repair, we have constructed mutants of the cyanobacterium Synechocystis sp PCC 6803 that are truncated at the exposed N terminus. Removal of 5 or 10 residues blocked D1 synthesis, as assessed in radiolabeling experiments, whereas removal of 20 residues restored the ability to assemble oxygen-evolving dimeric PSII complexes but inhibited PSII repair at the level of D1 degradation. Overall, our results identify an important physiological role for the exposed N-terminal tail of D1 at an early step in selective D1 degradation. This finding has important implications for the recognition of damaged D1 and its synchronized replacement by a newly synthesized subunit.
Keywords: mutace; financování organizované; biologické modely; posttranslační úpravy proteinů; Dimerization; Synechocystis; sekvence aminokyselin; podjednotky proteinů; Thylakoids; Structure-Activity Relationship; Molecular Sequence Data; Models, Biological; dimerizace; tylakoidy; Photosystem II Protein Complex; Mutation; Protein Processing, Post-Translational; Amino Acid Sequence; linkomycin; fluorescenční spektrometrie; fotosystém II (proteinový komplex); Light; Financing, Organized; Mutant Proteins; molekulární sekvence - údaje; Protein Structure, Secondary; mutantní proteiny; sekundární struktura proteinů; Protein Subunits; autotrofní procesy; vztahy mezi strukturou a aktivitou; světlo; Spectrometry, Fluorescence; Autotrophic Processes; Lincomycin